Adaptação transcultural do Self-Reported Experiences of Activity Settings (SEAS) para a Língua Portuguesa (Brasil) - Peruzzo, Caroline Fernanda Bella (2021)
Introduction: Engagement is defined in the literature as a multifaceted state composed of affec-tive, cognitive and behavioral aspects, conceptualized in two interrelated ways, as a process (in-volvement with) and a state (involved in). For occupational engagement to start, some points need to be considered, such as the sense of readiness, purpose or meaning, participation, motiva-tion and interest, while other points are seen as influencing the level of engagement, being the state of mental health and cognitive ability, challenge, feedback and environmental elements. The literature describes a conceptual model of “social environment” and “social context” that inte-grates a perspective focused on the person with a perspective focused on the environment and that outlines the mechanisms through which children and youth and the social environment inter-act: this is the Model of social environment and social context. This model directs researchers and professionals to interventions that address interaction, including children and their social en-vironments, families, peer groups and communities, in order to create possibilities for healthy development and the creation of health-promoting environments. In this perspective, the Self-reported Experiences of Activity Settings (SEAS) instrument was developed, which assesses the self-report of young people in relation to their activities. The instrument has good psychometric qualities and favorable results in its application. Objective: to carry out the cross-cultural adapta-tion of the Self-reported Experiences of Activity Settings (SEAS) to Portuguese (BRAZIL). Methodology: the cross-cultural adaptation of the instrument was carried out with the approval of the instrument's authors. From that approval, the steps taken were the initial translation, trans-lation synthesis, back-translation, evaluation by the expert committee and cognitive development. The cognitive development was carried out with 22 adolescents with and without physical disa-bilities, attended at institutions in medium-sized cities in the interior of São Paulo in order to veri-fy the understanding of the instrument's items. Results: The rate of agreement in the sentences by the committee of judges was satisfactory and the items below 80% of agreement were adjusted based on consensus among the researchers, corresponding to a total of 15 sentences. In the stage of cognitive development, it was observed that the Portuguese version was understandable be-cause the comprehension index was high for the adolescents in the study and the authors ap-proved the final version. Discussion: Certain occupational therapy terms used in SEAS are dis-cussed, such as “activity settings”. Differences in translation styles are also discussed, highlight-ing the importance of the stages of translation, back-translation, the composition of the expert committee at work and the results obtained in the stage of cognitive development. Conclusion: The results of the study demonstrated that the equivalence with the original version was main-tained and the instrument in Portuguese appears to be suitable for the Brazilian population. It ends with an instrument ready to undergo psychometric studies, in order to be validated for Bra-zil.